QUALITY CONTROL OF MINERAL OILS ON STAGES OF THEIR LIFE CYCLE - Demidko , V. G.; Drovnin , S. S.; Pashinsky, A. I. (Problems of Informatization and Management, 2021)
The application of the mass transfer method of dehydration of mineral oils in order to preserve their quality has been substantiated. A mathematical model of mass transfer dehydration of mineral oils has been developed. A dependence is obtained that takes into account the design features of the bubbling devices, the physicochemical properties of the liquid and gas. The parameters of the modes of treatment of mineral oils with inert gases have been determined.